1998
DOI: 10.1007/s100510050198
|View full text |Cite
|
Sign up to set email alerts
|

Critical phenomena at perfect and non-perfect surfaces

Abstract: The effect of imperfections on surface critical properties is studied for Ising models with nearest-neighbour ferromagnetic couplings on simple cubic lattices. In particular, results of Monte Carlo simulations for flat, perfect surfaces are compared to those for flat surfaces with random, 'weak' or 'strong', interactions between neighbouring spins in the surface layer, and for surfaces with steps of monoatomic height. Surface critical exponents at the ordinary transition, in particular $\beta_1 = 0.80 \pm 0.01… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
88
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(99 citation statements)
references
References 88 publications
10
88
1
Order By: Relevance
“…Similar agreement is also obtained for other O(n) models. From the numerical point of view, the best investigated cases are n = 0 [45,46] and n = 1 (Ising) [47,17,18,48,8], whereas studies for n ≥ 2 are scarce [24,49,50,51]. The rather few experimental determinations of surface critical exponents at the ordinary transition, using for example x-ray scattering at grazing angle, yield values which are found to be compatible with the theoretical estimates [52,53,54,55].…”
Section: The Surface Universality Classesmentioning
confidence: 69%
See 4 more Smart Citations
“…Similar agreement is also obtained for other O(n) models. From the numerical point of view, the best investigated cases are n = 0 [45,46] and n = 1 (Ising) [47,17,18,48,8], whereas studies for n ≥ 2 are scarce [24,49,50,51]. The rather few experimental determinations of surface critical exponents at the ordinary transition, using for example x-ray scattering at grazing angle, yield values which are found to be compatible with the theoretical estimates [52,53,54,55].…”
Section: The Surface Universality Classesmentioning
confidence: 69%
“…Kaneyoshi observed that the critical coupling ratio r sp is shifted to higher values in systems with a diluted surface and he conjectured that this is a common effect of surface amorphisation. This was confirmed by a Monte Carlo study [8] where the strength of surface bonds was chosen randomly between two different values J s1 and J s2 , the ratio d = J s1 /J s2 measuring the degree of dilution. For d = 1/10 the special transition point is located at the mean coupling ratio r sp = 1.7(0.1) for the simple cubic lattice, noticeably larger than the value obtained for the perfect surface r sp ≈ 1.5, see Section 2.1.…”
Section: Semi-infinite Systems With Surface Imperfectionsmentioning
confidence: 78%
See 3 more Smart Citations